Application of Virtual Reality and Augmented Reality in the Recruitment Process - Santos, Mariana; Carneiro, Andreia; Correia, Tiago; Costa, Daniel; Ferreira, Pedro; Figueiredo, Clara; Lopes, Liliana; Marques, António; Meirinhos, Viviana; Rodrigues, Ana Cláudia; Seixas, Daniela; Silva, Mariana; et al. (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
Technology has been shaping change in society, and work environment. Human resources management (HRM) has also affected and is also influenced by the digitalisation process. Virtual and augmented reality technologies are on the rise and used in many sectors (Thoondee & Oikonomou, 2017), as well as in HRM (e.g. Pan, Cheok, Yang, Zhu & Shi, 2006; Stanković & Savković, 2013). Virtual Reality (VR) recreates the sense of reality for an individual as if the person were physically present in a given environment (Hutchison, 2018). Augmented reality (AR) is a technology which overlays virtual objects (augmented components) into the real world, which seem to exist in the same room as objects from the real world (Akçayır & Akçayır, 2017). Given the war for talent, finding and engaging the people the organisation needs (Armstrong, 2014: 226), the recruitment process, has a crucial role in the competitiveness of the organisations. This paper presents a review of what has already been studied about VR and AR, as well as the potential of these technologies in the recruitment process.